Asimilasi Narapidana Di Lembaga Pemasyarakatan Terbuka Mataram - Sofian Hadi Sasmita (Fakultas Hukum Universitas Mataram, 2017)
The research aims to discuss Assimilation of Prisoners in Mataram Open Correctional Institution. The legal issue proposed in this research include How is the provision of assimilation for prisoners from prisons to the Mataram Open Correctional Institution. This study used normative legal research that examines the legal norms regarding the provision of assimilation from prisons to open prisons and stages of assimilation in the Mataram Open Correctional Institution. The approach of the thesis used legislation and conceptual approach. The technique of collecting legal materials are (1) literature study by systematically processing the legal material and (2) making known interpretations in law science to the laws and regulations relating to this research and the conclusion ultimately drawn deductively. The result of this script concludes that the assimilation requirement for prisoners is not the same but differentiated based on criminal acts committed by prisoners. The criminal acts are categorized into general crimes and special crimes which are included in